Catalytic regeneration of a Th–H bond from a Th–O bond through a mild and chemoselective carbonyl hydroboration. Issue 78 (14th September 2018) - Ghatak, Tapas; Makarov, Konstantin; Fridman, Natalia; Eisen, Moris S.
Abstract : Organoactinide-mediated chemoselective hydroboration of aldehydes and ketones. The catalytic regeneration of a Th–H bond from a Th–OR bond was achieved via hydroboration with HBpin. Abstract : Here we present an unprecedented chemoselective hydroboration for aldehydes and ketones catalysed by actinides. The reaction features a very low catalyst loading (0.1–0.004 mol%) and quantitative product formation in less than 15 minutes, at room temperature. Thermodynamic and kinetic studies including stoichiometric and labeling studies with deuterated pinacolborane allow us to propose a plausible mechanism for this remarkable catalytic regeneration of a Th–H bond via carbonyl hydroboration.